Ultrafast carrier dynamics in bimetallic nanostructure-enhanced methylammonium lead bromide perovskites. Issue 4 (9th January 2017) - Zarick, Holly F.; Boulesbaa, Abdelaziz; Puretzky, Alexander A.; Talbert, Eric M.; DeBra, Zachary R.; Soetan, Naiya; Geohegan, David B.; Bardhan, Rizia
Abstract : We investigate the interaction of bimetallic plasmonic nanostructures with methylammonium tribromide perovskites and probe the effects on charge separation and injection with transient absorption spectroscopy and time-resolved photoluminescence. Abstract : In this work, we examine the impact of hybrid bimetallic Au/Ag core/shell nanostructures on the carrier dynamics of methylammonium lead tribromide (MAPbBr3 ) mesoporous perovskite solar cells (PSCs). Plasmon-enhanced PSCs incorporated with Au/Ag nanostructures demonstrated improved light harvesting and increased power conversion efficiency by 26% relative to reference devices. Two complementary spectral techniques, transient absorption spectroscopy (TAS) and time-resolved photoluminescence (trPL), were employed to gain a mechanistic understanding of plasmonic enhancement processes. TAS revealed a decrease in the photobleach formation time, which suggests that the nanostructures improve hot carrier thermalization to an equilibrium distribution, relieving hot phonon bottleneck in MAPbBr3 perovskites. TAS also showed a decrease in carrier decay lifetimes, indicating that nanostructures enhance photoinduced carrier generation and promote efficient electron injection into TiO2 prior to bulk recombination. Furthermore, nanostructure-incorporated perovskite films demonstrated quenching in steady-state PL and decreases in trPL carrier lifetimes, providing further evidence of improved carrier injection in plasmon-enhanced mesoporous PSCs.